ISLAMIC ECONOMIC MODEL IN REDUCING GAP OF GROWTH AND UNEMPLOYEMENT - Kusnadi, Iwan; Sumar’in, Sumar’in (Hunafa: Jurnal Studia Islamika, 2018)
The theme of the article is based on economic principles of Islam. The purpose of research is to see economic development in the perspective of the Islamic economy especially research aims to analyze the effect of economic growth and unemployment in Indonesia period 1998-2017, a perspective of the Islamic economy. Economic development is one of the strategies to achieve the goals aspired nation. The goal is how poverty, unemployment, economic disparity and social resolved so as to realize human welfare. But in fact, the construction of which is expected to have an influence on society has not caused yet siding with the people. Increased poverty and unemployment occur. This type of research is an ex post facto. Technical documentation was applied for searching the data from Statistics Central Board, Indonesia Bank, BAPPENAS in Indonesia. Data analysis technique was Regression. Data analysis shows that: there is a negative influence toward economic growth in the rate of Indonesia and unemployment in 1998-2018. Economic development in Islamic economy perspective focus to three elements such as forbidden interest (ribā) as instrument financial, optimization zakat and characteristics of an element of spiritual, moral, and material, and activities tend to be multidimensional so that all business submitted to balance a variety of factors and does not cause inequality.